2006
DOI: 10.1139/h06-017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of differences in post-exercise lactate accumulation in athletes’ haemodynamics

Abstract: To verify the relationship between exercise intensity and post-exercise haemodynamics, we studied haemodynamic and lactate responses during 10 min following 3 bicycle tests. Two tests were performed for 3 min at 70% and 130% of the workload corresponding to anaerobic threshold (70% W(at) and 130% W(at) tests), and 1 was performed until exhaustion at 150% of the maximum workload achieved during a previous incremental test (150% W(max) test). During the recovery period after the 150% W(max) test we observed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 33 publications
3
19
1
2
Order By: Relevance
“…Our results are also similar to, which demonstrated that a larger exercise volume may cause a prolonged PEH. Some have hypothesized that PEH is caused by a combination of change in stroke volume and HR, while others have suggested a relationship of cBLa with systemic vascular resistance . However, we observed no difference in HR post‐exercise compared with pre‐exercise, and no difference in PEH despite a cBLa 2.3 times higher in 5RES compared with 3RES.…”
Section: Discussioncontrasting
confidence: 80%
“…Our results are also similar to, which demonstrated that a larger exercise volume may cause a prolonged PEH. Some have hypothesized that PEH is caused by a combination of change in stroke volume and HR, while others have suggested a relationship of cBLa with systemic vascular resistance . However, we observed no difference in HR post‐exercise compared with pre‐exercise, and no difference in PEH despite a cBLa 2.3 times higher in 5RES compared with 3RES.…”
Section: Discussioncontrasting
confidence: 80%
“…A greater accumulation of metabolites in the protocol with lower RI (30s) that had been demonstrated by Ratamess et al 18 and Crisafulli et al 28 could explain the longer post-exercise decrease in SBP and DBP that was found in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…However, as previously stated, we could not directly measure cardiac preload, since impedance cardiography cannot assess end-diastolic volume; this hypothesis remains speculative. The fact that venous and arteriolar dilation took place after ISDN is testified by Z 0 , which is an inverse index of thoracic fluid volume, that is, reductions in its values are associated with increases in central blood volume, whereas increases in Z 0 occur when central blood volume is reduced, such as during leg venous pooling (6,10,18). The reduction in this parameter indicated that an increase in thoracic blood volume was present after ISDN, a phenomenon coherent with the ISDN effects, i.e., artery and venous capacity vessel dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, NCCOM 3-derived analog traces of electrocardiogram, thorax impedance (Z0), and Z0 first derivative were stored by using a digital chart recorder (PowerLab 8sp; ADInstruments, Castle Hill, Australia). Z0 is an inverse index of thoracic fluid volume, since reductions in its values are associated with increases in central blood volume while increases in Z0 occur when central blood volume is reduced, such as during leg venous pooling (6,10,18). Hence, changes in Z0 were used as an indirect measure of changes in central blood volume.…”
Section: Methodsmentioning
confidence: 99%